Kontribusi Tanggung Jawab Sosial Perusahaan, Green Accounting, Kinerja Lingkungan terhadap Profitabilitas - Rahayu, Hesti; Akadiati, Victoria Ari Palma (Universitas Muhammadiyah Metro, 2025)
The research method used is quantitative with a sample of companies engaged in the manufacturing sector through purposive sampling techniques and data is processed using the SPSS application. The results of the study show that corporate social responsibility and green accounting do not have a significant effect on the profitability of companies in the manufacturing sector. Environmental performance has proven to have a significant positive influence on the profitability of manufacturing sector companies. This research provides benefits for investors in considering sustainability factors in investment decision-making, as well as for companies to improve social and environmental performance to support profitability. These findings can also contribute to the formulation of government policies that support corporate transparency and sustainability